Implementasi Program Pembiasaan dan Keteladanan pada Era New Normal dalam Membentuk Akhlak Siswa MTs Miftahul Huda, Tayu, Pati - Muhammad Amin (Islamic University of Indonesia, 2022)
The Covid-19 pandemic has caused such a huge impact on the education sector, any ongoing educational program must be temporarily suspended and adjusted to the situation so as not to endanger the community. This of course can be a potential for not achieving educational goals as they should. This study aims to describe how the implementation and efforts made by the madrasa in MTs Miftahul Huda, Tayu, Pati in running an exemplary program in shaping morals during the new normal. The research method usedis a qualitative approach with the type of field research, while the analysis used is descriptive analysis of the flow chart analysis model developed by Miles and Huberman. After collecting data using observation techniques, semistructured interviews, and documentation studies, the researchers managed to find that during the new normal period the exemplary habituation program was carried out with various adjustments. Through these adjustments, the program can be implemented optimally while still meeting strict procedures.Existing programs are designed with good management, through planning, implementation, and evaluation stages that are carried out systematically so that they are still able to meet the educational goals that have been previously planned despite being hampered by the Covid-19 pandemic.